PENERAPAN TEKNOLOGI MANAJEMEN PENGELOLAAN SAMPAH DI KAMPUNG INSPIRASI JATIBARU DESA JATIENDAH, KABUPATEN BANDUNG - Raharja, Apriadi Budi; Pirngadi, Budi Heri; Darmawan, Fajar (Jurnal Abdi Insani, 2024)
The active participation of all community members in managing waste in the RW 17 neighborhood of Jariendah Village, Cilengkrang District, Bandung Regency, is like an "oasis" of community-based waste management in 2010. It has become an inspiration for all levels of society to gain experience in waste management. However, one of the partners' problems includes data and recording problems that have not been properly structured. For this reason, the dedication to the partners we appoint is the need to improve the efficiency of digital-based waste management. Digitalization in waste management is important for partners to increase effectiveness in recording transactions, reporting changes in the price of waste commodities, and increasing customer data. The method chosen for implementing Community Service to solve this institutional problem is the Focus Group Discussion (FGD) method and mentoring, which consists of five stages of activities. At the end of this service activity, UPK has a waste management application. Users can already use waste management applications that benefit from data and information for community-based waste management activity programs.